Resilience: A commentary from the vantage point of anthropology. Issue 1 (May 2016) - BARRIOS, ROBERTO E.
Abstract : In recent years, the concept of resilience has gained popularity as a means to describe the qualities and capacities that enable a community to recovery from a catastrophic event. Definitions of resilience make a number of assumptions about the nature of communities and the practices that enable their ability to cope or weather a disaster's impact. In this article, I provide a brief history of the ways disaster researchers have defined resilience and provide an analysis of the fundamental assumptions upon which such definitions are based. Furthermore, I provide a critical analysis of such assumptions in light of anthropological knowledge about the relationships and processes that put communities on the map, shape the ways they are exposed to hazards, and their possibilities for recovery. In conclude by providing four recommendations for practice which stress 1) the recognition of disaster has a historically shaped process involving development practice and human‐environment relations, 2) the recognition of the broader political ecological relationships that shape resilience, 3) an emphasis on systemic transformation rather than locality specific interventions as a means of resilience‐building, and 4) a prioritization of subaltern voices in operationalizations of "rebuilding better" as a mechanism for addressing the practices of environmental injustice that routinely give form to disaster vulnerability and those conditions that are branded "low resilience."